Eliminating Sectoral Ego in Law Enforcement: Integrating Whistleblowing Systems for Corruption Eradication in the Indonesian Judicial System - Selamat Widodo; Astika Nurul Hidayah; Ika Ariani Kartini; Kiki Kristanto (Jurnal Dinamika Hukum, 2026)
Corruption in Indonesia's judicial system remains a persistent structural problem, exacerbated by sectoral egos among law enforcement agencies and the fragmentation of existing mechanisms for reporting violations. Currently, the reporting system is not implemented in an integrated manner, thereby weakening coordination, undermining legal protection for whistleblowers, and creating procedural loopholes that facilitate impunity. This study aims to analyse the urgency of integrating the violation reporting system among law enforcement agencies as a strategic tool to eradicate corruption in the judicial system. Using a normative legal research methodology with a conceptual approach, this study combines a sociological-legal approach with empirical data from corruption case reports, institutional policies, and secondary data from anti-corruption agency reports from year to year. Although each law enforcement institution in the criminal justice system has its own whistleblowing mechanism, these remain fragmented, so integration is needed to enable mutual oversight, overlapping authority, and weak coordination between agencies, which reduces the effectiveness of corruption detection and eradication. An integrated reporting system, supported by comprehensive regulations and adequate whistleblower protection mechanisms, can improve transparency, accountability, and inter-agency coordination. This study concludes that eliminating sectoral egos through regulatory harmonisation and digital integration of reporting systems is a prerequisite for sustainable judicial reform. It is recommended that the government establish a centralised and interoperable reporting system.